2022
DOI: 10.2298/hemind220609018t
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hazardous waste a case study of electric arc furnace dust characterization

Abstract: Dust from an electric arc furnace is formed as the main by-product of the steel production process from the secondary iron-based raw materials. This dust has significant contents of Zn and Fe, as well as Pb, Cd, Ca, Mg, Cr, Mn, Si, Ni, Cu, F, Cl and other elements and is considered hazardous industrial solid waste since it contains heavy metals. In order to protect the environment and public health from the negative impact of this type of hazardous waste, it is necessary, even mandatory, to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Based on the results obtained by chemical analysis (Table 2), it can be concluded that the analyzed sample of EAF dust contains a large number of elements, which confirms the complexity of EAF dust as a material. In addition, the obtained results are in agreement with the literature [4,6,7,12,23,28]. The highest abundance in the sample is zinc with a content of 32.38%, followed by iron with 28.28%, while other elements, such as Cl, Ca, Mn, Pb, Ni, Cu, Cr, Cd, Na, K, F, Ti, P, and others, are less abundant in the analyzed EAF dust sample.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Based on the results obtained by chemical analysis (Table 2), it can be concluded that the analyzed sample of EAF dust contains a large number of elements, which confirms the complexity of EAF dust as a material. In addition, the obtained results are in agreement with the literature [4,6,7,12,23,28]. The highest abundance in the sample is zinc with a content of 32.38%, followed by iron with 28.28%, while other elements, such as Cl, Ca, Mn, Pb, Ni, Cu, Cr, Cd, Na, K, F, Ti, P, and others, are less abundant in the analyzed EAF dust sample.…”
Section: Resultssupporting
confidence: 90%
“…Based on the obtained results of the granulometric analysis, it was determined that 70 wt.% of the sample consists of particles of size <31 µm, which indicates the possibility of a difficult filtering process during the hydrometallurgical process of the EAF dust treatment. The obtained results of the particle size distribution of the EAF dust sample are in agreement with the literature [3,28,45].…”
Section: Particle Size Distributionsupporting
confidence: 91%
See 3 more Smart Citations